2011
DOI: 10.1055/s-0030-1270741
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeability of the Constituents from the Roots ofSaposhnikovia divaricatain the Human Caco-2 Cell Monolayer Model

Abstract: The bidirectional intestinal permeability of the active constituents from the roots of Saposhnikovia divaricata, including four coumarins, anomalin (1), 5-methoxy-7-(3,3-dimethylallyloxy)coumarin (2), decursin (3), and decursinol angelate (4), as well as four chromones, cimifugin (5), prim-O-glucosylcimifugin (6), 3'- O-angeloylhamaudol (7), and sec-O-glucosylhamaudol (8), was studied by using the Caco-2 cell monolayer. These compounds were assayed by HPLC, and their transport parameters, including apparent pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…However, its aglycone cycloastragenol can be absorbed through intestinal epithelium efficiently . This is similar to prim-O-glucosylcimifugin, 4 0 -O-b-glucopyranosyl-5-O-methylvisamminol, and their aglycone cimifugin Xue et al, 2000;Zhao et al, 2011). It has been reported that changes in telomere lengths are relevant to immune function (Weng, 2012), and cycloastragenol upregulates telomerase activity (Fauce et al, 2008;Ríos, 2010;Yung et al, 2012).…”
Section: Results Of Pharmacokinetic Studysupporting
confidence: 54%
See 1 more Smart Citation
“…However, its aglycone cycloastragenol can be absorbed through intestinal epithelium efficiently . This is similar to prim-O-glucosylcimifugin, 4 0 -O-b-glucopyranosyl-5-O-methylvisamminol, and their aglycone cimifugin Xue et al, 2000;Zhao et al, 2011). It has been reported that changes in telomere lengths are relevant to immune function (Weng, 2012), and cycloastragenol upregulates telomerase activity (Fauce et al, 2008;Ríos, 2010;Yung et al, 2012).…”
Section: Results Of Pharmacokinetic Studysupporting
confidence: 54%
“…It has been used for preventing viral infections including severe acute respiratory syndrome (Lau et al, 2005;Poon et al, 2006), and is reported to have immunoregulatory and beneficial effects in allergic rhinitis, asthma, and dermatitis models (Fang et al, 2005;Makino et al, 2004Makino et al, , 2005Nakatsukasa et al, 2009). Phytochemical and serum pharmacochemical analyses have found that YPFS contains isoflavones from Radix Astragali and chromones from Radix Saposhnikoviae as major constituents (Huang et al, 2008;You, 2007;Zhao et al, 2011;Zheng et al, 2011). In Radix Astragali, astragalosides have been identified as potential bioactive compounds via intestinal absorption and cell extraction studies (Xu et al, 2006;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among 9 phytochemistry papers with in vitro studies [8][9][10][11][12][13][14][15][16] , 5 [11,[13][14][15][16] were selected based on their relevance, but the phytochemistry component did not adhere to the selection criteria. A total of 10 in vitro studies only were included in this review [17][18][19][20][21][22][23][24][25][26] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Psoraleae fructus is commonly used in Chinese to alleviate asthma [22]. Other herbs [23]-[29], Codonopsis radix, Cuscutae semen , Schisandrae chinensis fructus . Citri reticulatae pericarpium , and Saposhnikoviae radix , have also been shown to have effective anti-inflammatory activities and modulated immune responses, which may also exert a preventive effect in allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%